PREPARATION, EVALUATION AND BIOAVAILABILITY STUDIES OF PROPAFENONR HYDROCHLORIDE LOADED WITH GUM MICROSPHERES FOR CONTROLLED STUDY - ANJANA JOHN; ZEINUL HUKUMAN; D.V.GOWDA (International Journal of Pharma and Bio Sciences, 2013)
The objective of the present study was to prepare the propafenone Hydrochloride(P) loaded into natural and modified gums microspheres by emulsification solvent evaporation technique utilizing wetting agent. Effect of different process variables on drug loading studies during the preparation of microspheres was optimized. Sieve analysis data indicated that the prepared microspheres were in the range of 106 to 500 μm. The angle of repose, % Carr’s index and tapped density were well within the limit, indicating reasonable good flow potential for the prepared microspheres.SEM photomicrographs and sphericity factor confirms the prepared formulations are spherical in nature. DSC studies and FTIR spectra showed that the encapsulated drug was stable in the prepared formulations. XRD studies revealed the crystalline nature of the drug. Drug discharge from prepared formulations were studied and compared with commercially available controlled release formulation Rhothmonorm® ER - 225 mg. It was observed that, there was no significant release of drug at gastric pH. Drug release kinetics from the formulations followed different transport mechanisms. From the results, P loaded Modified Locust bean gum (PXML1) A single dose randomized two period cross over study was conducted to compare the pharmacokinetics and bioavailability of P (225mg) from test formulation (product B – PXML1 - P loaded MLBG) with standard formulation (Product A - Rhothmonorm® ER - 225 mg capsule). The observed mean values Tmax, Cmax, AUC0 -∞, Ka. T half and Kel for products A & B does not show any significant statistical difference. From the dissolution point and invivo bio availability for products A & B could be considered bio equivalent. The drug release performance was greatly effected by the materials used in the microsphere preparation which allows maximum absorption in the intestine.